1984
DOI: 10.1073/pnas.81.3.979
|View full text |Cite
|
Sign up to set email alerts
|

Motor deficits in patients with large-fiber sensory neuropathy.

Abstract: The issue of whether brain signals in the absence of peripheral feedback are sufficient to specify accurate movement was evaluated by studying motor performance in patients with loss of somesthetic afferent input as a result of acquired large-fiber sensory neuropathy. With visual guid-ance, movements and postures were impaired relatively little, but when visual guidance was unavailable, the patients exhibited postural drift and gross inaccuracy of movement. Impairments were more apparent for smaller (3°) than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
147
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(155 citation statements)
references
References 16 publications
7
147
1
Order By: Relevance
“…According to this notion, an increase of viscosity opposing the movements of both normal and deafferented subjects would alter the intended velocity during movement from the initial to the terminal position, but would have no effect on intended terminal accuracy. These considerations underlie the theoretical implications of recent findings that deafferented humans fail to position a limb accurately after a viscous load is introduced during movement (Day and Marsden, 1982;Rothwell et al, 1982a;Sanes, 1983;Sanes et al, 1985). As mentioned above, if CNS signals in the absence of somesthetic feedback were able to specify movement end-points, then a change of viscous loading would alter movement trajectory but would not affect movement end-point.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…According to this notion, an increase of viscosity opposing the movements of both normal and deafferented subjects would alter the intended velocity during movement from the initial to the terminal position, but would have no effect on intended terminal accuracy. These considerations underlie the theoretical implications of recent findings that deafferented humans fail to position a limb accurately after a viscous load is introduced during movement (Day and Marsden, 1982;Rothwell et al, 1982a;Sanes, 1983;Sanes et al, 1985). As mentioned above, if CNS signals in the absence of somesthetic feedback were able to specify movement end-points, then a change of viscous loading would alter movement trajectory but would not affect movement end-point.…”
mentioning
confidence: 99%
“…This suggests that triggered muscle responses are compensatory in certain movement situations but disruptive in others. In addition, these findings demonstrated that dynamic loads especially affect the kinematics and end-point control of smaller movements, suggesting that kinesthetic inputs and central motor commands interact so subjects may achieve accurate positioning for certain classes of movements.Several recent studies of motor control in patients with sensory loss have described impairments of movement accuracy as a result of viscous-load changes occurring during movement (Day and Marsden, 1982;Nam et al, 1984;Rothwell et al, 1982a;Sanes et al, 1985). The reason for the use of viscous loads (as compared to springs or weights) in these studies was that viscous loads acted during displacement but not during absence of movement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is much indirect evidence that the telencephalon participates in "programming" voluntary behavior (Bernstein, 1967;Rothwell et al, 1982Rothwell et al, , 1989Carter and Shapiro, 1984;Marsden et al, 1984;Sanes et al, 1985;Ghez et al, 199 I), including the findings that many different neurons in the telencephalon are more active before and during movement (Evarts, 1968;Brinkman and Porter, 1979;Bock et al, 1987;Humphrey and Freund, 1991;Mushiake et al, 1991;Kalaska et al, 1992). However, little evidence exists that localize a particular motor program to a discrete telencephalic brain area (Alexander et al, 1992).…”
mentioning
confidence: 99%
“…The results showed that stimulation decreased cutaneous sensory function as evidenced by increased touch threshold. Absolute dorsiflexion force on visual feedback to maintain accuracy (Rothwell et al 1982;Sanes et al 1984). In order to achieve fine force resolution in finger control, cutaneous feedback must be properly integrated with central motor command (Henningsen et al 1995(Henningsen et al , 1997.…”
Section: Introductionmentioning
confidence: 99%